Floxuridine-containing nucleic acid nanogels for anticancer drug delivery. Issue 18 (3rd May 2018) - Ma, Yuan; Liu, Hongxia; Mou, Quanbing; Yan, Deyue; Zhu, Xinyuan; Zhang, Chuan
Abstract : Herein, we report the self-assembled floxuridine-containing DNA and RNA nanogels with a precise drug loading ratio as effective drug delivery systems. Abstract : Herein, we report the self-assemblies of floxuridine-containing DNA and RNA nanogels with a precise drug loading ratio as effective drug delivery systems. Based on the structural similarity between the nucleoside analogue floxuridine (F) and the natural nucleoside thymidine (T), F can be incorporated into nucleic acid strands via either solid-phase synthesis or enzyme-mediated transcription. With the retained property of molecular recognition, the synthesized F-integrated DNA or RNA strands can be used as building units and further assembled into nucleic acid based spherical nanogels, which can be efficiently taken up by cancer cells and then release the therapeutic agents. As such, the drug-containing nucleic acid nanogels exhibit excellent inhibitory activity against cancer cells.